1992
DOI: 10.1177/002224299205600205
|View full text |Cite
|
Sign up to set email alerts
|

Servicescapes: The Impact of Physical Surroundings on Customers and Employees

Abstract: A typology of service organizations is presented and a conceptual framework is advanced for exploring the impact of physical surroundings on the behaviors of both customers and employees. The ability of the physical surroundings to facilitate achievement of organizational as well as marketing goals is explored. Literature from diverse disciplines provides theoretical grounding for the framework, which serves as a base for focused propositions. By examining the multiple strategic roles that physical surrounding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

42
1,687
1
148

Year Published

1996
1996
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 2,935 publications
(2,106 citation statements)
references
References 38 publications
42
1,687
1
148
Order By: Relevance
“…A salesperson's satisfaction with sales territory design relates significantly to job satisfaction and performance (Grant et al 2001). In addition, the office environment represents the servicescape within which many of the customer exchanges take place and which has important implications for both client and salesperson outcomes (Bitner 1992). Extensive interviews with the firm's management, support service providers, and salespeople indicated that the new office opening process, which lasts several months, is a critical event in a salesperson's career.…”
Section: Methodsologymentioning
confidence: 99%
“…A salesperson's satisfaction with sales territory design relates significantly to job satisfaction and performance (Grant et al 2001). In addition, the office environment represents the servicescape within which many of the customer exchanges take place and which has important implications for both client and salesperson outcomes (Bitner 1992). Extensive interviews with the firm's management, support service providers, and salespeople indicated that the new office opening process, which lasts several months, is a critical event in a salesperson's career.…”
Section: Methodsologymentioning
confidence: 99%
“…How these norms can be imbued in the context of one's environment has been largely unexplored as a tool to alter behavior at an aggregate level. Existing laboratory research [4], and applied research in health [5], education [6], and organizational [7] and consumer [8] behavior have converged on the notion that modifying contextual factors may be an effective way to shape behavior. These results raise the exciting possibility that context can serve as a means to promote environmentally conscious behavior outside the lab and in everyday life.…”
Section: Introductionmentioning
confidence: 99%
“…The researchers suggested innovative design and style approaches to develop the atmosphere of facilities. Physical environment quality may affect the cognitive/emotional states and buying behaviours of customers (Donovan and Rossiter, 1982; Wakefield et al, 1996), as the majority of services utilised by consumers within the physical facility are produced and consumed all at the same time (Bitner, 1992). It was stated that the event service experiences of customers focused on sports facilities during the sport and recreational services (Westerbeek, 2000).…”
Section: Discussionmentioning
confidence: 99%